Serious Games - The challenges for computer science in sport - Wiemeyer, J. (International Journal of Computer Science in Sport, 2010)
Digital games can be used not only for fun and entertainment. The term `serious games` denotes digital games serving serious purposes like education, training, advertising, research, and health. In the contribution the chances and challenges of serious games for computer science in sport will be discussed. Serious games, particularly adventure and shooter games, already play an important role in health education and rehabilitation, e.g., to enhance healthrelated physical activity, prevent asthma, change nutrition behavior and alleviate diabetes, prevent smoking or HIV. Serious games also offer new options for training in sport. In our laboratory, we developed a prototype for application in volleyball training. Education in sport and sport science is another promising application field of serious games. Particularly the natural sciences offer the opportunity to combine simulations and gaming in order to learn about the basics of movement. The effects of Serious Games depend on the specific game genre. They can be described and explained by different mechanisms including social, psychological, and motor processes. Despite first promising results the sustainability is a critical factor. In this regard, computer science in sport can help to develop and implement serious games and test appropriate settings that ensure sustainable use of serious games.